Yeats et le mélange des genres : du texte à la scène - Pierre Longuenesse (Sillages Critiques)
In the « Theatre of Imagination » conceived by Yeats in the 1890s, the poetic Verb is given the power of creating visions through the concrete physicality of its uttering by the performing body of what Georges Banu will later call an « acteur-poète ». This project transforms dramatic writing process into the creation of a multiform object, in which the issue of the drama is brought out by the tension between opposite medium : theatre on the one hand, singing, dance, tale on the other hand… This exploration involves Yeats into original collaborations on stage with composers, musicians, and dancers. In short, those manifestations of an artistic « hors-champ », far from  threatening the drama, become on the contrary the core of its expression, as a new power is, on stage, devoted to the Verb : the extra-ordinary power to arise the pneuma of singing as well as the rhythm of the dancing body.